O-90 Randomised controlled trial of joint crisis plans to reduce compulsory treatment for people with psychosis: Clinical outcomes and implementation. (1st September 2015) - Thornicroft, G; Farrelly, S; Szmukler, G; Birchwood, M; Waheed, W; Flach, C; Barrett, B; Byford, S; Henderson, Claire; Sutherby, K; Lester, H; Rose, D; et al.
Abstract : Background: A Joint Crisis Plan (JCP) aims to empower patients whilst facilitating early detection and treatment of relapse. Two studies have suggested that JCPs might reduce compulsory treatment and improve therapeutic relationships. Aim: The CRIMSON randomised controlled trial compared JCPs with treatment as usual for people with severe mental illness. Methods: Eligibility criteria were: at least one psychiatric admission in the previous two years and on Enhanced Care Programme Approach register. The settings were 64 community mental health teams. The intervention was the JCP, a negotiated statement by a patient of treatment preferences for any future psychiatric emergency. Hypotheses tested were that, compared to the control group, the intervention group would experience: (1) fewer compulsory admissions; (2) fewer psychiatric admissions; (3) shorter psychiatric stays; (4) lower perceived coercion; (5) improved therapeutic relationships; and (6) improved engagement. Results: 569 participants were randomised (285 experimental, 284 control group). No significant treatment effect was seen for the primary outcome (56 (20%) in the control arm and 49 (18%) in the JCP arm; odds ratio 0.90 (95% CI 0.58 to 1.39,  p = 0.63) or admissions outcomes, however there was evidence for improved therapeutic relationships (17.3 (7.6) v 16.0 (7.1); adjusted difference –1.28 (95% CI –2.56 to –0.01, p = 0.049). Qualitative data supported this finding. Discussion: The results contrast with two earlier studies. There is evidence to suggest the JCPs were not fully implemented in all sites. Conclusion: The study raises important questions about implementing new interventions in routine practice.